Airbreathing Propulsion An Introduction - Bose, Tarit. (Springer Aerospace Technology, 2012)
Airbreathing Propulsion covers the physics of combustion, fluid and thermo-dynamics, and structural mechanics of airbreathing engines, including piston, turboprop, turbojet, turbofan, and ramjet engines. End-of-chapter exercises allow the reader to practice the fundamental concepts behind airbreathing propulsion, and the included PAGIC computer code will help the reader to examine the relationships between the performance parameters of different engines. Large amounts of data on many different piston, turbojet, and turboprop engines have been compiled for this book and are included as an appendix. This textbook is ideal for senior undergraduate and graduate students studying aeronautical engineering, aerospace engineering, and mechanical engineering.